Detection of early cleavage embryos improves pregnancy and delivery rates of Day 3 embryo transfer during in vitro fertilization - Chun-I Lee; Tsung-Hsien Lee; Chun-Chia Huang; Hsiu-Hui Chen; Chung-Hsien Liu; Maw-Sheng Lee (Elsevier, 2016)
Objective: This study established a simple criterion for improving the pregnancy and delivery rates of Day 3 embryo transfer for in vitro fertilization (IVF) by assessing the early cleavage of two-cell stage embryos. Materials and Methods: In total, 258 cycle patients undergoing an IVF and Day 3 embryo transfer program were recruited. All cycles were divided into four groups containing viable Day 3 embryos and those (A) with distinct early cleavage (equal-sized blastomeres and ≤10% fragmentation: ECA grade); (B) with indistinct early cleavage (equal sized blastomeres, >2 blastomeres, or >10% fragmentation: ECB grade); (C) without early cleavage [no early cleavage (NEC grade)]; or (D) without early cleavage being assessed (control) at 25-27 after insemination. Results: The percentage of viable Day 3 embryos from ECA grade (75.1%, 507/675) was significantly higher than that from ECB grade (19.2%, 151/403) or NEC grade (27.1%, 127/469) embryos (p < 0.01). The pregnancy and delivery rates in the ECA group [65.7% (65/990) and 48.5% (48/990), respectively] were significantly higher than those in the ECB group [30.8% (4/13) and 7.7% (1/13), respectively] or NEC group [36.8% (14/38) and 23.7% (9/38), respectively; all p < 0.01]. The implantation rate in the ECA group (32.3%, 129/400) was higher than those in the ECB (6.8%, 4/59) and NEC (13.0%, 18/136) groups (p < 0.01). Conclusion: Simple selection using the early cleavage morphology may improve the pregnancy and delivery rates of Day 3 embryo transfer programs.